Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.5812/aapm.118424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Two Doses of Dexmedetomidine on Sedation, Agitation, and Bleeding During Pediatric Adenotonsillectomy

Abstract: Background: Due to the importance of dexmedetomidine and its different dosages, here, we aimed to investigate and compare the effectiveness of the doses of 1 µg/kg and 2 µg/kg of dexmedetomidine in sedation, agitation, and bleeding in pediatrics undergoing adenotonsillectomy. Methods: This double-blinded randomized clinical trial was performed on 105 pediatric patients that were candidates for adenotonsillectomy. Then, the patients were divided into three groups receiving dexmedetomidine at a dose of 2 µg/kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 28 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Existing studies related to neuroprotection are limited by heterogeneity that limits broad applicability. Many of the studies reviewed included pediatric patients undergoing elective procedures at low risk, ranked as American Society of Anesthesiologists (ASA) Physical Status Classification System class I or II ( 91 , 92 , 94 , 95 , 97 , 98 ). Future studies including high risk patients undergoing major surgeries and emergency surgeries with higher ASA classes may be included to contribute to the data and research in the application of dexmedetomidine for neuroprotection in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing studies related to neuroprotection are limited by heterogeneity that limits broad applicability. Many of the studies reviewed included pediatric patients undergoing elective procedures at low risk, ranked as American Society of Anesthesiologists (ASA) Physical Status Classification System class I or II ( 91 , 92 , 94 , 95 , 97 , 98 ). Future studies including high risk patients undergoing major surgeries and emergency surgeries with higher ASA classes may be included to contribute to the data and research in the application of dexmedetomidine for neuroprotection in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine also has a role in treating emergence agitation (EA) in the pediatric population. Shafa et al compared the effectiveness of two distinct doses of dexmedetomidine (1 μg/kg and 2 μg/kg) versus placebo in treating agitation, which was measured using PAEDS in pediatric patients undergoing adenotonsillectomy ( 97 ). The researchers found that the use of dexmedetomidine at both doses was associated with a significant reduction in agitation upon emergence ( 97 ).…”
Section: Emergence Delirium and Emergence Agitation In Pediatric Pati...mentioning
confidence: 99%
See 1 more Smart Citation